PENERAPAN KOMBINASI INHALASI PEPPERMINT OIL DAN FISIOTERAPI DADA UNTUK MENINGKATKAN BERSIHAN JALAN NAFAS PADA ANAK BALITA DENGAN ISPA DI RUMAH SAKIT DEWI SRI KARAWANG (STUDI KASUS) - Desty Lismayanti; Yanti Rosmiyanti; Sumitro Sumitro; Sarini Sarini; Okti Rahayu Asih; Aditia Rahmat Hidayat (Journal of Innovation Research and Knowledge, 2025)
Acute Respiratory Infection (ARI) is one of the most common health problems among toddlers and may lead to ineffective airway clearance due to the accumulation of respiratory secretions, which is characterized by coughing, shortness of breath, increased respiratory rate, and adventitious breath sounds. This study aimed to describe the implementation of a combination of peppermint oil inhalation and chest physiotherapy in improving airway clearance among toddlers with Acute Respiratory Infection at Dewi Sri Hospital Karawang. This study employed a case study method involving two toddler patients who experienced ineffective airway clearance. The intervention was administered for three consecutive days, and observations were conducted on respiratory rate, dyspnea, and adventitious breath sounds. The results showed an improvement in airway clearance in both subjects. In the first subject, the respiratory rate decreased from 42 breaths per minute to 35 breaths per minute, while in the second subject it decreased from 45 breaths per minute to 39 breaths per minute. In addition, dyspnea was reduced, secretion clearance became more effective, and adventitious breath sounds in the form of rhonchi decreased. Based on these findings, it can be concluded that the combination of peppermint oil inhalation and chest physiotherapy is effective in improving airway clearance among toddlers with Acute Respiratory Infection. This intervention may serve as an alternative non-pharmacological nursing intervention to help reduce secretion accumulation and improve respiratory function in toddlers